Festival and Competition Movement as A Form of Development of Teacher’s and Student’s Dialogical Thinking - Koptseva, Tatyana (2020)
The relevance of the problem examined in the study is determined by the insufficient knowledge from the point of modern pedagogics of art about the widely spread and publicly recognized festival and competition movement which is aimed at identifying gifted children and promoting the aesthetic development of all children participating in festivals and competitions in various types of art. Following the priorities of modern education aimed at the formation of students’ independent thinking, creativity, tolerance, initiative, and communicability, the authors view the festival and competition movement as a form of development of dialogical thinking in teachers and students able to understand each other in the process of communicating on the topics of art, creativity, and social phenomena. The basis of the study is formed by the results of four children’s drawing competitions held by the Federal State Research Institution of the Russian Academy of Education “Institute of Art Education” in 2019-2020 which involved 30 educational institutions and over 3,000 drawings, as well as teachers’ reports and video and photographic recordings of the educational process and programs combining all types of participants’ artistic activity (musical, theatrical, literary, fine art, decorative, constructive, design) at the final stages of festivals and competitions. The dialogue of arts practiced in the process of children’s and teachers’ participation in the festival and competition movement is disclosed in the present article as a method of dialogical thinking development manifesting in creative activity that has a motive, a goal, a system of actions and operations, a result and control. The goal of the study is to identify the aesthetic and personal priorities of children and adolescents in various types of art that allow determining the optimal system of motives, goals, actions, and operation in the course of the dialogue between a teacher and a student on the topics of art, creativity, and social and cultural events. It is concluded that the festival and competition movement presents an effective form of development of teacher’s and student’s dialogical thinking under certain conditions, namely the reliance on the age-specific and individual characteristics of a child’s development, the formation of “I am the author” position in a child, and a teacher’s understanding of a student’s aesthetic and personal priorities.